Lags and leads in life satisfaction: a test of the baseline hypothesis - Andrew E. Clark; Ed Diener; Yannis Georgellis; Richard E. Lucas (Institute for the Study of Labor (IZA), 2006)
We look for evidence of habituation in twenty waves of German panel data: do individuals, after life and labour market events, tend to return to some baseline level of wellbeing? Although the strongest life satisfaction effect is often at the time of the event, we find significant lag and lead effects. We conclude that there is complete adaptation to divorce, widowhood, birth of first child, and layoff. However, adaptation to marriage is only incomplete, and there is no adaptation to unemployment for men. In general, men are more affected by labour market events (unemployment and layoffs) than are women. Last, we find no consistent evidence that happiness provides insurance against hard knocks: those with high and low baseline satisfaction levels are broadly equally affected by labour market and life events.
urn:nbn:de:101:1-20080429143
Keywords: 330; Lebensqualität; Lebensverlauf; Erwerbsverlauf; Familiensoziologie; Deutschland